Detection of methicilline resistant staphylococcus aureus carrying mecc gene in mastitic milk samples of cattle in turkey - Zafer Sayın; Aslı Sakmanoğlu; Uçkun Sait Uçan; Yasemin Pınarkara; Ali Uslu; Zeki Aras; Osman Erganiş (Eurasian Journal of Veterinary Sciences)
Aim: It was aimed to investigate the mecC gene in phenotypically methicillin-resistant Staphylococcus aureus (MRSA), isolated from mastitic milk samples. Materials and Methods: This study was performed on 150 S. aureus strains isolated from mastitic cattle. Resistance to methicillin was determined by cefoxitin disc diffusion method and commercial PBP2a latex agglutination test. Detection of mecA and mecC gene in MRSA isolates were carried out by Polymerase Chain Reaction (PCR). Results: Twenty eight (18.6%) out of 150 S. aureus isolates were identified phenotypically as MRSA by cefoxitin disc diffusion test. Aglutination and mecA gen were detected in 21 (75%) MRSA isolates by latex agglutination test and PCR, mecC gene was determined in 7 (25%) MRSA isolates in all of which no positivity by latex agglutination test and mecA-PCR analysis was observed. Conclusion: mecC MRSA isolation rate was determined as to surprisingly be high in mastitic cattle in Turkey, and mecC gene should also be further analyzed for genotypic confirmation of MRSA isolates that already identified by phenotypic methods.